Adolescent Perceptions of Help-intended Acts of Peer Helpers - McDowell, Christina Anne (Canadian Journal of Counselling and Psychotherapy, 2011)
Adolescent perceptions of the counsellor effectiveness of peer helpers were examined by studying perceptions of videotaped simulated interviews. The subjects were 143 grade eleven students. The effects of training (trained versus untrained) and role label ( friend versus peer counsellor ) were tested. Counsellor effectiveness was assessed using the following measures: Counselor Rating Form (Barak & LaCrosse, 1975), Tape Assisted Recall Categories of Help-Intended Acts (Elliot, 1979), and Helpfulness (Cooker & Cherchia, 1976) and standardized interviews. Significant results for the effect of training were found on the following five variables: understanding (p < .001), attractiveness (p <.004), reassuring (p <.005), gathering information (p < .001), and guiding (p < .001). Data indicates that adolescents perceive trained peer helpers as more facilitative than untrained helpers, supporting the training and use of adolescent peer counsellors.